Clinical and Radiological Characteristics of Non-Benign Pineal Cyst Lesions in Children - Arkar, Ula; Kučan, Rok; Perković Benedik, Mirjana; Hostnik, Tadeja; Vipotnik Vesnaver, Tina; Loboda, Tanja; Bošnjak, Roman; Osredkar, Damjan (Frontiers in Neurology, 2021)
Background: With the increasing availability and advances in brain imaging, pineal cyst lesions (PCL) are becoming a common finding in the pediatric population. In the absence of evidence-based guidelines, optimal diagnostic and therapeutic approaches have not been established, and there is a risk of under- or overtreatment of these patients. Objectives: The aim of our study was to evaluate the clinical presentation and radiological features of PCL in a cohort of pediatric patients and to identify clinical parameters more commonly associated with neoplasms in the pineal region. In addition, the prevalence of PCL in the pediatric population of Slovenia was estimated. Methods: In this observational, cohort study, children treated at University Children's Hospital, Ljubljana, Slovenia in the period 1997–2016 were included if PCL was found on brain imaging. We analyzed indications for referral to a neurologist, clinical signs and symptoms, radiological features, treatment and outcome. Results: The cohort consisted of 143 children with PCL. Pineocytoma was suspected in 31 children (21.7%). Six children underwent surgery – pineocytoma was confirmed in two cases and germinoma in one (2/3 of these children had signs of increased intracranial pressure (ICP), while PCL was benign in the remaining 4 cases. Only 2 PCL enlarged during the study period, both <2mm, none of these children developed neoplasm. Two children had PCL >20mm in diameter; both showed signs of increased ICP, one patient was found to have a germinoma of the pineal region, while the other had no neoplasm. Conclusions: Most PCL do not change their features during radiological follow-up and even atypical PCL are very rarely associated with a malignant neoplasm of the pineal region. A PCL larger than 20 mm and signs of increased ICP were identified as potential markers for selecting patients at risk.